Central and peripheral blood pressures and arterial stiffness increase in hypoparathyroidism - Pamuk,Naim (2020)
ABSTRACT Objective The aim of the present study was to evaluate whether arterial stiffness is affected in the patients with hypoparathyroidism through pulse wave analysis (PWA). Subjects and methods Sixty-three patients diagnosed with hypoparathyroidism and sixty volunteers were evaluated for the study. When 21 patients were excluded in the hypoparathyroidism group due to exclusion criteria, the research continued with 42 patients and 60 volunteers who are similar to the patients in terms of age, gender and body mass index (BMI). Fasting plasma glucose after 10 hours of fasting, creatinine, thyroid stimulating hormone (TSH), free thyroxine (fT4), albumin, calcium, phosphorus, magnesium, 25-OH vitamin D, parathormone (PTH) and urine calcium results in 24-hour urine for the patients in the hypoparathyroidism group were recorded. Evaluation of arterial stiffness was performed by Mobil-O-Graph 24h PWA device. Results Systolic blood pressure (SBP) (p = 0.01), diastolic blood pressure (DBP) (p = 0.005), mean blood pressure (p = 0.009), central SBP (p = 0.004), central DBP (p = 0.01) and pulse wave velocity (PWV) (p = 0.02) were found higher in the hypoparathyroidism group. A positive correlation was detected between phosphorus level and SBP [(p = 0.03. r = 0.327)], central SBP [(p = 0.04, r = 0.324)] and PWV [(p = 0.003, r = 0.449)]. We detected that age and serum phosphorus levels were independent predictor variables for PWV (B = 0.014, p < 0.001 and B = 0.035, p < 0.001, respectively). Conclusion We detected that hypoparathyroidism causes an increase in blood pressure and arterial stiffness. The most significant determinant factors were detected as advanced age and hyperphosphatemia. The patients diagnosed with hypoparathyroidism should be closely monitored and treatment planning should include to prevent the patients from hyperphosphatemia.